2016
DOI: 10.3762/bjoc.12.7
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular polymer assembly in aqueous solution arising from cyclodextrin host–guest complexation

Abstract: SummaryThe employment of cyclodextrin host–guest complexation to construct supramolecular assemblies with an emphasis on polymer networks is reviewed. The main driving force for this supramolecular assembly is host–guest complexation between cyclodextrin hosts and guest groups either of which may be discrete molecular species or substituents on a polymer backbone. The effects of such complexation on properties at the molecular and macroscopic levels are discussed. It is shown that cyclodextrin complexation may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 115 publications
(138 reference statements)
1
20
0
Order By: Relevance
“…[28] For a given CD, there are three monosubstituted, dozens of disubstituted, and more than one hundred trisubstituted isomers possible. [50][51][52][53][54] The number of known monosubstituted CD derivatives is enormous and their listing would exceed the scope of this review. The efforts spent on this work have paid off, and many selectively multiply substituted CDs have been prepared.…”
Section: General Methods For Synthesis and Characterisation Of Monosumentioning
confidence: 99%
“…[28] For a given CD, there are three monosubstituted, dozens of disubstituted, and more than one hundred trisubstituted isomers possible. [50][51][52][53][54] The number of known monosubstituted CD derivatives is enormous and their listing would exceed the scope of this review. The efforts spent on this work have paid off, and many selectively multiply substituted CDs have been prepared.…”
Section: General Methods For Synthesis and Characterisation Of Monosumentioning
confidence: 99%
“…18 The special molecular structure of b-CD consists of a hydrophobic inner core and a hydrophilic outer shell, making it can selectively incorporate a plenty of hydrophobic molecules as the guest into its cavity to form host-guest inclusion complex. [19][20][21] Moreover, some research have indicated that the introduction of b-CD into copolymer backbone can exhibit remarkable salt-resistance and temperature-tolerance, 22,23 which ensure its can be applied to oil eld for EOR.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Each CD molecule consists of a hydrophobic inner core and a hydrophilic outer shell, making it possible to include the hydrophobic moieties of the polymer and form inclusion complex. 26,27 Several host-guest polymer systems based on CD modied polymer for enhanced oil recovery were proposed in recent years. [28][29][30][31] Based on the hostguest interaction, CD modied acrylamide polymers can enhance the polymer-polymer association then increasing the viscosity of the system while CD monomers can inhibit the association.…”
Section: Introductionmentioning
confidence: 99%